International law and its discontents : confronting crises - Stark, Barbara, 1952- (Cambridge : Cambridge University Press, 2015)
In Civilization and its Discontents, Sigmund Freud argued that civilization itself is the major source of human unhappiness, inhibiting instincts and generating guilt. In Globalization and its Discontents, Joseph Stiglitz shows how the'economic architecture' that produced globalization has also driven the backlash against it. This book brings together some of international law's most outspoken'discontents'; those who situate their malaise in international law itself. Their shared objective is to expose international law's complicity in the ongoing economic and financial global crises and to assess its capacity - and its will - to constructively address them. Some, like Freud, view that which holds us together as an inevitable source of discontent. Others, like Stiglitz, draw on the energy of the backlash. How have these crises affected particular groups, sovereign states, and international law itself? How have they responded? When does crisis serve as a catalyst, and for what?
Machine generated contents note: Part I. The Environment: 1. Binge development in the age of fear: scarcity, consumption, inequality and the environmental crisis Ileana Porras; 2. International law as a war against nature? Karin Mickelson; Part II. Gender: 3. Decoding crisis in international law: a queer feminist perspective Dianne Otto; 4. The incredible shrinking women Barbara Stark; Part III. Sovereign States: 5. Corporate power and instrumental states: toward a critical reassessment of the role of firms, states and regulation in global governance Dan Danielsen; 6. Global economic inequality and the potential for global democracy: a functionalist analysis Andrew Strauss; Part IV. International Political Crisis: 7. A Bolivarian alternative? The new Latin American populism confronts the global order Brad Roth and Sharon F. Lean; 8. Global crises and the law of war Jeanne Woods.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Law -- Social aspects; Law -- Economic aspects; Comparative law; International law and human rights